Geotechnics for Transportation Infrastructure Recent Developments, Upcoming Technologies and New Concepts, Volume 1 - Sundaram, Ravi.; Shahu, Jagdish Telangrao; Havanagi, Vasant; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents selected papers from the International Symposium on Geotechnics for Transportation Infrastructure (ISGTI 2018). The research papers cover geotechnical interventions for the diverse fields of policy formulation, design, implementation, operation and management of the different modes of travel, namely road, air, rail and waterways. This book will be of interest to academic and industry researchers working in transportation geotechnics, as also to practicing engineers, policy makers, and civil agencies.
Theme 1: Challenges in design and construction of pavements and embankments -- Theme 2: Design and construction of substructures for highways, high speed railway and metro track projects -- Theme 3: Advances in bridge foundations, waterways, airfields and pipeline transport geotechnics -- Theme 4: Slope stability, landslides, debris flows and avalanches on hilly roads and remedial measures -- Theme 5: Subsurface sensing, investigations and monitoring in transport geotechnics -- Theme 6: Use of geosynthetics and non traditional materials in transport geotechnics -- Theme 7: Transport geotechnics in underground construction -- Theme 8: Ground improvement techniques for transport geotechnics -- Theme 9: Emerging trends in transport geotechnics- Unsaturated Soil Mechanics, Macro and Nano Technology, Climate Change and Sustainability.
Keywords: Engineering geology; Transportation engineering; Traffic engineering; Geotechnical engineering; Geoengineering; Transportation Technology and Traffic Engineering; Geotechnical Engineering and Applied Earth Sciences